Sobre el uso y origen del concepto «Escuela de Salamanca» - Martín Gómez, María (Scripta theologica, 2023)
The "School of Salamanca", as a historiographical concept, has been discussed in relation to its dating, the members who would be part of it and its characteristics. This paper analyzes the emergence and the origin of this concept in the nineteenth and twentieth centuries with the purpose of knowing if the characteristics that were given to this group of thinkers when for the first time they were spoken of as a school, can clarify some of the debates that are taking place today.